Budaya Demokrasi di Sulawesi Selatan: Perspektif Strukturasi - Muchid Albintani (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This paper was presented as an attempt to understand the relationship of culture and democracy in the contemporary era [political reform] in perspective Structuration in Sulawesi Selatan. Cultural relations and democracy as a political system becomes an important era of reforms ongoing regime. In this context, political culture can be a pattern for rebuilding a democratic political behavior, especially that coming, raised and developed from the values of the local community, such as in Sulawesi Selatan. From this culture can be the foundation to build democracy ‘patterned’ local. Based on this argument paper is aimed at, [i] Identify and analyze the interaction of the instruments ‘culture of democracy’ in the contemporary Sulawesi Selatan. [i]. Formulating a contemporary democratic culture in South Sulawesi. To help explain and answer relationship with the democratic culture used the theory of Democracy, Political Culture and Structuration. The review of this paper shows that [i] Instruments and cultural interaction of democracy that exists in Sulawesi Selatan, Wajo Eclectic is a form of government, a special selection mechanism that leaders and representatives tiered, based on the relationship of the people and leaders of law as well as agreements made together. Furthermore, the interaction between these instruments indicate if the form of government, election mechanism as well as representatives and leaders of government’s relationship with its people have significance to the structure [political institution], not the actor or elite with ties to the past. [ii] Based on these conditions, the formulation of political culture in the era of political reform [contemporary era] in Sulawesi Selatan is characterized by [a] The strong primordial and paternalism and, [b] Culture conflictual still strong, do not show the cultural values inherited from the previous., Based on this argument appears that the structure remain more influential actor who should have the value of integrity and independence.